Analysis of the paradigm of economic development of Kazakhstan via S. Sadvokasov’s views - Mukanova, G. (Journal of Economic Research & Business Administration, 2021)
The article draws attention to the historical parallels between the general tasks of state self-identity, which were solved by the government at the start of acquiring the sovereign status of the Republic of Kazakhstan in 1991, and those strategic problematic issues that should have been regulated by the government of the Kazakh autonomy at the stage of 1920-1926. Unfortunately, despite the relevance of the topic, there are practically no special comparative studies in the bibliography for establishing continuity in the practice of regulating the economic development of Kazakhstan within the dichotomy of 1921 – 2021. The purpose of the study is to revive the names and activities of the leading leaders from among the Kazakh leaders who have dropped out of the history of the Fatherland, on the basis of interdisciplinary methods and archival sources. The article describes the contribution of Smagul Sadvokasov to the strategy of economic development of the region, provides rare facts from the history of training personnel of the domestic railway transport. The scientific and practical significance of the work is in updating the topic of national and state identity and replenishing the biography of the leader of the Kazakhstani management elite, Chairman of the State Planning Committee S. Sadvokasov, who became victims of repression. The systematization of rare data, carried out by the author of the article, of the past determines the modern directions of integration solutions, for the sake of national interests, in the context of the practical experience of previous generations. Key words: Kazakhstan, economy, risks, integration, autonomy, Sadvokasov Smagul.